al-Barnāmaj al-nawawī al-Īrānī wa-al-mutaghayyirāt fī amn al-khalīj / taʾlīf Mamdūḥ Ḥāmid ʻAṭīyah, ʻAbd al-Raḥmān Rushdī al-Hawwārī, Muḥammad Jamāl al-Dīn Maẓlūm ; murājaʻat Jalāl ʻAbd al-Fattāḥ. - ʻAṭīyah, Mamdūḥ Ḥāmid. (Alf kitāb (al-thānī), 2003)
Nuclear energy; nuclear weapons; Iran; government policy; military policy.